Ascorbic Acid Based Controlled Growth of Various Cu and cu2o Nanostructures - Singh, D; Barraza-Aguilera, N; Enríquez-Montenegro, J; Vivas, L; Chi-Duran, I (IOP PUBLISHING LTD, 2019)
Here we report a facile and fast ascorbic acid based controlled growth of various nanostructures of Cu and Cu2O by varying the concentration of NaOH. Ascorbic acid being a weak reducing agent not only slows down the reaction kinetics but also provides a better control for the self-assembly of nanostructures. Cu and Cu2O nanoparticles are synthesized by chemical reduction of copper nitrate (Cu(NO3)(2) x 2.5 H2O) with different concentration of NaOH (0.01, 0.1, 0.5, 1.0, 5.0 and 10 M) solution in the presence of ascorbic acid. The low concentrations of NaOH (0.01 and 0.10 M) result the formation of almost pure phase of Cu nanoparticles. Whereas the higher concentrations (0.5, 1.0 and 5 M and 10 M) result into formation of pure nanocubes, truncated octahedron, polygon shaped and finally spherical shaped Cu2O particles respectively.